Evaluation of inpatient cases with alcohol and drug use between years of 1998 and 2002 - Saatçioğlu, Ömer; Evren, E. Cüneyt; Çakmak, Duran (Journal of Dependence, 2003)
Objective: Characteristics of inpatients with alcohol and drug use, changes of these characteristics and determining areas alcohol and drug use influence are important factors at approaches of treatment and course in addiction.Method: All patients had inpatient treatment at Alcohol and Drug Research, Treatment and Education Center (AMATEM) in Bakirkoy Research Hospital for Psychiatric and Neurological Diseases between years of 1998 and 2002. The data of 6526 patients who were taken from AMATEM data bank was retrospectively determined by using records of semi structured questionnaire.Results: In the evaluation of 5 years’ data, the ratios of sex (female: 4,2-4,9 % and male: 95,1-95,8%) and education level were similar between all years. We found that the most common reason for seaking treatment was alcohol use and alcohol was firstly and most widely used substance among inpatients in all of years. The fact that the range of age at first use of a drug was low as 6 to 10 years was the one of the most important results of the study (2,1-3,3%). On the other hand, the range of age that alcohol and drug use was the most prevalent was between 21 to 30 years. The methods of drug use in each year were different and the rate of drug use as intravoustly was the lowest in 2002 compared to the other years. The rate of social and health problems related to drug use was found to be night.Conclusion: We found that sociodemographic and alcohol-drug use characteristics, and life time problems did not significantly change during fire years among inpatients in AMATEM. Some important issues on application and observation of inpatients with alcohol and drug use were discussed.
Keywords: Alcohol; drug; addiction